QOL-55. HOME PHYSICAL ACTIVITY INTERVENTION TO IMPROVE COGNITIVE LATE EFFECTS IN CHILDREN TREATED WITH RADIATION FOR BRAIN TUMORS: DESCRIPTIVE FEASIBILITY DATA FROM A PILOT RANDOMIZED CONTROLLED TRIAL (RCT). Issue 2 (22nd June 2018) - Wolters, Pamela; Abel, Cristina; Martin, Staci; Smith, Kevin; Toledo-Tamula, Mary Anne; Roderick, Marie Claire; Drinkard, Bart; Chen, Kong; Kramer, Arthur; Schembri, Adrian; Han, Joan; Glod, John; et al.
Abstract: Cranial radiation therapy (CRT) contributes to cognitive late effects that require rehabilitative interventions. Physical activity (PA) targets CRT-damaged brain mechanisms and cognitive functions. We conducted a pilot RCT to evaluate the feasibility of an innovative home PA intervention program for children treated with CRT for brain tumors. Eligible children 8-17 years, >two years post-CRT, with cognitive late effects were randomized to the Intervention Group (IG), which followed a 12-week home program to increase PA then maintained PA for 12 weeks, or the Control Group (CG), which monitored usual PA for 12 weeks followed by the 12-week program. Psychologists taught Acceptance and Commitment Therapy (ACT) techniques to facilitate PA engagement. Participants used Zamzee accelerometers/website to track moderate-to-vigorous PA (MVPA). Evaluations included plasma/serum circulating growth factors, cardiovascular fitness, cognitive function pre/post the first 12 weeks, and child/parent feasibility questionnaires (1-5 ratings, categories, open-ended questions). Six children (mean age=13.8 years, 10-17; IG=3; CG=3) enrolled and completed the study. Participants enjoyed the activity tracker (mean=3.8) and wore it 3-4 times/week to daily, but it broke easily; most liked the website's activity graphs, rewards, and challenges (mean=3.3; uploaded data/viewed <1 to 4 times/week). Children rated the ACT sessions/emails lower (mean=2.6) although goal-setting was used consistently. Most frequent self-selected PAs were running, walking, and basketball. Participants liked the program (mean=4.1) and found it helpful (mean=4.0); 6/6 increased their weekly MVPA (total means 41 to 130 minutes). These pilot data suggest good feasibility but indicate aspects of the home PA intervention to revise for the full RCT.